The peculiarities of the professional self-determination of the PTEE students - Bonchuk, Nataly (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
This article concerns the problem of self-determination of the Professional Technica l Educational Establishment students. The results of empirical research of students’ professional self-determination are presented and its components are highlighted and analyzed. In the limit of each component, the social and psychological factors are studied, which influence a formation of the professional “I”. It is identified that these factors might be as the ones corresponding the professional self-determination, so as the ones conflicting with it. It is ascertained that the part of the components of the professional self-determination of the PTEE students is formed under the in fluence of such motives not directly connected to the situation of a realized professional choice, development of a certain competence, realization of peculiar interests etc., and has go t the characteristics of accidence, situational, adaptation to the life’s circumstances. The analysis of the professional self-determination in the layer of components is proposed as the means of valuation of a perspective professional selection and an education of optants.